Why Macro and Trade Sometimes Fail the Poor: The Role of Food Price Instability - Timmer, Peter (2015)
"IFPRI at 40: Looking Back, Looking Forward" Special Event held on November 18, 2015. Presentation by Peter Timmer, Emeritus Professor of Development Studies at Harvard University.